The occurrence of sclerotium rot on Momordica charantia caused by Sclerotium rolfsii in Korea. (25th February 2016) - Kwon, Jin-Hyeuk; Kang, Dong-Wan; Choi, Okhee; Kim, Jinwoo
Abstract : Sclerotium rolfsii is one of the most destructive pathogens and thought to affect a broad range of plant hosts. In July 2014, an occurrence of sclerotium rot was observed on bitter melon ( Momordica charantia L.) in Jinju, South Korea. The rot symptoms were most developed on stems and fruit near the soil line, and infected bitter melon plants withered and eventually died. White mycelial mats with numerous sclerotia were produced on diseased stems and fruit near the soil surface. Based on the morphological characteristics, pathogenicity tests, and DNA sequencing and phylogenetic analysis of the internal transcribed spacer (ITS) ribosomal RNA (rRNA) gene region, the causal fungus was identified as S. rolfsii Saccardo. This is the first report of sclerotium rot caused by S. rolfsii on bitter melon in Korea. The recent occurrence of sclerotium rot on bitter melon poses a potential threat to its production in Korea.